Inculcating Character Values Through History Learning - Hasnadi, Hasnadi; Inayatillah, Inayatillah (SCAD Independent, 2022)
The development of a country is determined by the character of its citizen. Character education is very strategic if developed through education in schools. The history lesson is one of the right subjects to inculcate character values to students. This article aimed to describe the implementation of character values through history learning. The method of writing used was library research. The implementation of character values through history learning can be performed in the following ways; (1) designing a learning implementation plan (LIP) by including the character values to be developed by the core competence, competence standard, basic competence, content standard, and achievement indicators intended, (2) History teachers used the already compiled LIP as a guideline in delivering the lesson. The process of learning was carried out in an active, innovative, creative, effective, interesting, and fun manner centered on the students. The character values applied and developed in all activities involved in the learning process were evaluated in a systematic, measurable, and sustainable way, (3) The result from teachers’ observation and notes concerning students’ character during the learning process could be used as a basis of evaluation toward the attainment of character values implementation. Evaluation results can serve as a consideration and a conclusion describing the profile of students’ character as well as a foundation in determining follow-up actions.